An immersed boundary approach for high order weighted essentially non-oscillatory schemes. (30th May 2021) - Di Mascio, Andrea; Zaghi, Stefano
Highlights: A new immersed boundary approach for high-order Godunov-type schemes is proposed. The scheme is easily applied to both Cartesian grid and general chimera-type grids. The scheme is applied and tested with WENO schemes up to seventh order of accuracy. Abstract: A new immersed boundary approach for high order Weighted Essentially non-Oscillatory (WENO) schemes is proposed. The schemes is based on the main ideas from both the general immersed boundary algorithms and the level-set approach and can be easily applied to both finite difference and finite volume formulation. Although formally only second order accurate, numerical tests prove that the use of higher order approximation for the Eulerian fluxes can be very convenient to capture flow details and to obtain low uncertainty also with very coarse grids.